2012
DOI: 10.13040/ijpsr.0975-8232.3(9).3001-06
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Pregnancy can be the most paranormal and exciting time for expectant mother. Nature provides us with many tools for supporting both the mother and baby through this time of growth and renewal, to strengthen the spirits and body to promote a healthy pregnancy and birthing process. Pregnant and lacting mother need to be educated on the need for caution when using herbs during pregnancy and lactation particularly in view of lack of complete information. The women self administer herbal medicines both before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…12 In like manner, the use of partridgeberry is considered as safe during labor; it is considered to tone and strengthen the uterus, resulting in more uniform uterine contractions. [29][30][31]33,34 Motherwort is said to be a fine uterotonic as it promotes a calming influence, relieves pain, and prevents miscarriage. 29 However, even though some sources report that motherwort can be used safely during pregnancy and to ease birth, 29,33 is has also been reported to be unsafe for use during pregnancy as it may cause birth defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 In like manner, the use of partridgeberry is considered as safe during labor; it is considered to tone and strengthen the uterus, resulting in more uniform uterine contractions. [29][30][31]33,34 Motherwort is said to be a fine uterotonic as it promotes a calming influence, relieves pain, and prevents miscarriage. 29 However, even though some sources report that motherwort can be used safely during pregnancy and to ease birth, 29,33 is has also been reported to be unsafe for use during pregnancy as it may cause birth defects.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, even though some sources report that motherwort can be used safely during pregnancy and to ease birth, 29,33 is has also been reported to be unsafe for use during pregnancy as it may cause birth defects. 34 Cramp bark, the remaining herbal ingredient in the labor induction tincture, has not been historically reported as a uterotonic. Instead, it is claimed to sedate the uterus and reduce the pains caused by uterine contractions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women with pre-existing conditions like epilepsy and asthma are at increased risk of potential herb-drug interactions. Besides, theoretical concerns exist about some herbs' teratogenic or embryotoxic effects [83,84].…”
Section: Undesirable Health Outcomesmentioning
confidence: 99%
“…Antinutrients were not considered as a factor in any of the human trials involving fenugreek, since the quantities were not large enough to influence the outcomes of the studies, though there were a few reported cases of allergy symptoms (Patil, Niphadkar, & Bapat, 1997). Normally, subjects who have demonstrated allergies to legumes are usually excluded from human trials and studies suggest that large amounts of fenugreek may cause uterine contractions, miscarriage, or premature labor (Shinde, Patil, & Bairagi, 2012) as well as estrogenic activity (Sreeja, Anju, & Sreeja, 2010).…”
Section: Antinutritional Compounds Present In Sainfoin and Fenugreekmentioning
confidence: 99%